Is TV a dying medium? - Binet, Les (Henry Stewart Talks, 2009)
3 myths about TV advertising, The effectiveness of TV: findings from the IPA dataBANK, Why TV works so well, The importance of broadcast media, The importance of fame, The importance of emotion
Archived at 2022/04/07